文档介绍:第一章多项式习题解答
17 262
fx()=−+− gx ()( x ) ( x−)
1) 39 9 9
2
2) fx()=+−+− gxx ()( x 1)(5 x+ 7)
23 2
1) x +−mx1| x ++⇒ 9 x q 余式(1pmxqm+ ++−= )( )0
⎧ mq=
∴⎨ 2
⎩ pq=−1
方法二,
32 ⎧ mq−= 0
x++=+−+⇒ pxqx(1)() m xq ⎨
设⎩−mq−=1 p 同样。
242 22
2 ) x ++mx1| x + px +⇒ q 余式 mp(2+ −−−++= m )( x q p 1 m )0
2 22
∴mm(2)+− p =0. mp+ =+1,(1 qx =− pq + )
53
用 g()xx=+ 3除 f ()xxx=−− 2 5 8x
解:
∴ fx( )=+− 2( x 3)54 30( x ++ 3) 175( x +− 3) 3 495( x ++ 3) 2 667( x +− 3) 327
.2)
∴()xx32−−x
32
=−++−(12)(28)(12)x iix −+i
−+(12 8ix )( −+−− 1 2 i ) (9 8 i )
即余式−98+ i
2
商 x −−+2(52ix i)
5
.
P44 ). fx()= x , x0 = 1:即
5432
∴ fx( )=−+−+−+−+−+ ( x 1) 5( x 1) 10( x 1) 10( x 1) 5( x 1) 1
55
当然也可以 fx( )== x [( x −+ 1) 1]
54
=−(1)5(1)xx + −+⋅⋅⋅+1
2) 结果
42 4 3 2
fx( )=− x 2 x +=+ 3 ( x 2) − 8( x + 2) + 22( x + 2) − 24( x ++ 2) 11
3)
43 2
f ()xx=+ 2 ixixx −+ (1) +++ 3 7 i
=+−+()2()(1)()3()7x ii43 ixii +−−+ ixii +−− 2 xii +−++ i
43 2
=+()2()(1)()5()75xi − ixi +++ ixi + − xi +++ i
22
(1) gx()=−( x 1)( x ++=− 2 x 1)( x 1)( x + 1)
3
xxxxf −−+= )13)(1()(
∴((f x),())g xx=+ 1
32
(2) gx()=− x 3 x + 1不可约
34
xxxf +−= 14)( 不可约
∴()fxgx(),()= 1
4 2 2 2
(3) xxxxxxxf −−−+=+−= )122)(122(110)(
432 32 2 2
gx()=− x 42 x + 6 x + 62 x + 1,() f x = 42( −+ x 22 x += x ) ( x − 22 x − 1)∴
()f (),()xgx=− x2 2 2 x − 1
22 22
(1) xxxf −+= )2()1()( gx()= ( x−++ 2)( x x 1)
22
∵(1)(1)(xxxxx+−+++++=[ ] 1)(2)1
2
∴(2)(1)()(2)(x −=−+xfxxgx ++ )
23 2
(2) −−+−= yxxxxxf )1424)(1()( , gx()= ( x−+− 1)(2 x x 4)
−= 1 xfx )()1( = (1)(x − gx1 )
而
fx11()=⋅ gx ()2-3(2 x x + 3)
gx1()=+⋅−(2 x 3)( x 1)
21x
1(23)(1)=x +xg −−111 = ( yfxg −)(1) −−1
∴ 33
122
x −=−1(1)()(xfxx −+2 − xgx − 1)()
∵ 333
234 2
(3) )( xxxxxf ++−−= 144 , gx()= x−− x 1
2
∴ fx()=−+ gxx ()( 3)( x− 2), gx()= ( x−++ 2)( x 1)1
2
∵1(=−f −gx ( − 3))(1)